Assessing Contextual Mathematical Literacy of Nautical Cadets Using PISA Proficiency Levels: Evidence from Maritime Vocational Education - Novitasari Novitasari; Eka Nurmala Sari Agustina; Atika Tirzha Sabrina Anggraeni (Universitas Islam Lamongan, 2026)
Mathematical literacy is a crucial competence in maritime education, supporting navigation accuracy, operational efficiency, and safety-related decision-making. However, empirical studies assessing mathematical literacy within authentic maritime vocational contexts remain limited. This study investigates the contextual mathematical literacy of nautical cadets using the PISA proficiency framework embedded in authentic maritime work-related scenarios. A quantitative descriptive design was employed with 23 cadets from a maritime vocational institution. Data were collected through a Contextual Mathematical Literacy Test (CMLT) developed using authentic maritime operational tasks. Descriptive and non-parametric analyses examined proficiency distributions and group differences. The findings indicate that most cadets perform at low to medium proficiency levels, highlighting the need for context-based and PISA-oriented mathematics instruction aligned with professional maritime demands.